Application of a zirconium-based metal organic framework material in the preparation of raw lacquer polymerization catalyst
By using a composite material of zirconium-based metal organic frame material UiO-66 (Zr) and corrosion inhibitor BTA, the problem of temperature and humidity limitations in the film formation process of raw paint is solved, and rapid film formation within a wider humidity range is achieved and anti-corrosion performance is improved.
Patent Information
- Application Number
- CN202310754435.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-06-26
AI Technical Summary
The process of raw paint film formation is limited by temperature and humidity, resulting in strict film formation conditions, and it is prone to aging and cracking outdoors, poor adhesion, poor alkali resistance, and difficult to quickly polymerize film formation.
The zirconium-based metal organic frame material UiO-66 (Zr) is used as a catalyst, and the corrosion inhibitor BTA is encapsulated in a MOF material to form a BTA@UiO-66 (Zr) composite material for catalyzing rapid film formation of raw paint.
Catalyzed raw paint quickly polymerizes the film into a wider relative humidity range, which improves the anti-corrosion performance and corrosion duration of the coating, enhances physical and mechanical properties, and solves the problems of strict film formation conditions and poor alkali resistance of raw paint.
Smart Images

Figure CN116987413B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of raw lacquer polymerization catalysts, and in particular to application of a zirconium-based metal organic framework material in the preparation of raw lacquer polymerization catalysts. Background Art
[0002] Metal materials refer to metal elements or materials with metal properties that are mainly composed of metal elements, including pure metals, alloys, intermetallic compounds and special metal materials. Due to their outstanding physical and process properties, metal materials are considered to be the most widely used structural materials and the main raw materials for industrial and agricultural production, national defense construction, and transportation.
[0003] Since pure metal materials are not completely stable, the oxidation state after corrosion is the stable state in which metal materials can exist permanently. Therefore, metal corrosion is also widely present in daily life. Metal corrosion refers to the phenomenon of metal corrosion caused by chemical, electrochemical or physical effects between metal materials and the environmental medium in which they are located. Nowadays, the main methods of metal corrosion protection include coating protection, electrochemical protection, and corrosion environment suppression.
[0004] Among them, raw lacquer (RL) is a commonly used natural metal anticorrosive coating in the coating protection method, in which the content of urushiol is about 60-80%, and the content of lacquerase is less than 1%. The coating is a milky white emulsion that flows out from the cut of the phloem of the sumac tree. It has excellent properties such as chemical stability, corrosion resistance, insulation, and bright luster. It is currently the only natural green coating in the world that can be used directly without special treatment.
[0005] Laccase is the key to the film formation of raw lacquer, but the catalytic action of lacquer is affected by the reaction medium, such as pH, solvent, oxygen pressure, temperature, etc. Therefore, the film formation requirements of raw lacquer are relatively strict, and it needs to be under a certain temperature and humidity (relative humidity above 80%, temperature 20-30 O C) can be carried out, otherwise the anti-ultraviolet absorption capacity of the paint film is poor. Ultraviolet rays can break the carbon bonds of lacquer phenol, and the polymer structure is degraded and destroyed. Aging and cracking are prone to occur outdoors. In addition, it has poor adhesion to metals, poor alkali resistance of the coating, is not easy to spray, and the formation time of the paint film is long at natural room temperature, and there are also shortcomings such as sensitization, which seriously restricts the application of raw lacquer. With the rapid development of modern industrial technology, how to make natural raw lacquer get rid of the temperature and humidity restrictions and quickly polymerize into film is still a problem to be solved in the raw lacquer industry, and it is also a severe challenge faced by the development of high-performance raw lacquer anti-corrosion coatings. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide an application of a zirconium-based metal organic framework material in the preparation of a raw lacquer polymerization catalyst, which is used to improve the film-forming conditions of the raw lacquer and catalyze the rapid film-forming of the raw lacquer.
[0007] The present invention is achieved in that:
[0008] The invention provides an application of a zirconium-based metal organic framework material in preparing a raw lacquer polymerization catalyst.
[0009] Furthermore, the zirconium-based metal organic framework material is UiO-66 (Zr).
[0010] Furthermore, the preparation method of UiO-66(Zr) is as follows: zirconium chloride and terephthalic acid are dissolved in anhydrous DMF solution, and then the solution is placed at 120 O C for 24 h, and after natural cooling, the solid was washed and centrifuged several times with methanol, dried, and finally placed at 120 O C in a vacuum drying oven for 12 h to obtain UiO-66(Zr).
[0011] Furthermore, the zirconium-based metal organic framework material is used as a carrier, and a corrosion inhibitor is added and encapsulated in the material.
[0012] Furthermore, the loading amount of the corrosion inhibitor is 0-5%.
[0013] Furthermore, the corrosion inhibitor includes benzotriazole BTA.
[0014] Furthermore, the packaging process is as follows:
[0015] UiO-66(Zr) was dissolved in DMF solution, and then BTA was added and mixed evenly. The mixture was stirred at room temperature for 12 h, and then centrifuged and washed with methanol several times. The solid powder obtained after centrifugation was collected and heated to 50 °C. O C in a vacuum drying oven for 10 h and ground to finally obtain the BTA@UiO-66(Zr) composite material.
[0016] On the other hand, the present invention also provides the use of the lacquer polymerization catalyst in preparing quick-drying lacquer, which is to mix the natural lacquer with the lacquer polymerization catalyst and stir them evenly.
[0017] Furthermore, the addition amount of the raw lacquer polymerization catalyst is 1-5%, preferably 3%.
[0018] The present invention has the following advantages: the present invention uses MOF material UiO-66 (Zr) instead of laccase to catalyze the film formation of raw lacquer, and uses the porous characteristics of MOF material as a carrier, introduces a corrosion inhibitor, encapsulates it in the MOF material, and then evenly disperses it in the raw lacquer to prepare a coating. The metal organic framework material can be used as a catalyst to improve the film formation conditions of the raw lacquer and catalyze the rapid film formation of the raw lacquer, and can also be used as a carrier of the corrosion inhibitor, so that the corrosion inhibitor does not affect the curing of the raw lacquer coating, and the corrosion inhibitor can also be released when the coating is damaged to form a protective film, further protecting the raw lacquer coating and improving its anti-corrosion performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.
[0020] Figure 1 XRD diffraction patterns of UiO-66(Zr) and BTA@UiO-66(Zr).
[0021] Figure 2 Infrared spectra of UiO-66(Zr) and BTA@UiO-66(Zr).
[0022] Figure 3 This is the SEM image of UiO-66(Zr).
[0023] Figure 4 SEM images of the coatings of RL(a1), RL-U-3(b1), and RL-BU-3(c1) at 75% RH, RL(a2), RL-U-3(b2), and RL-BU-3(c2) at 85% RH, and RL(a3), RL-U-3(b3), and RL-BU-3(c3) at 98% RH.
[0024] Figure 5 The infrared spectra of RL, RL-U-3 and RL-BU-3 coatings cured at 85% RH.
[0025] Figure 6 Impedance diagrams of RL, RL-U-3, and RL-BU-3 coatings at different times after curing at 85% RH.
[0026] Figure 7 Tafel curves of RL, RL-U-3 and RL-BU-3 coatings. DETAILED DESCRIPTION
[0027] 1 Technical Solution
[0028] 1.1 Preparation of UiO-66(Zr)
[0029] Weigh 1.225 g zirconium chloride and 0.881 g terephthalic acid in 60 mL of anhydrous DMF solution and stir with a magnetic stirrer for 30 min. Then transfer to a 100 mL polytetrafluoroethylene liner and place in a kettle at 120 O C constant temperature oven for 24 h, and after natural cooling, wash with methanol several times and centrifuge. O C oven for 12 h and finally placed at 120 O C in a vacuum drying oven for 12 h to obtain UiO-66(Zr).
[0030] 1.2 Preparation of BTA@UiO-66(Zr)
[0031] Weigh 0.1 g of the prepared UiO-66(Zr) and dissolve it in 40 mL of DMF solution, then add 0.4 g of BTA and mix well, stir at room temperature for 12 h, then centrifuge at 6000 rpm for 10 min, wash with methanol several times, collect the solid powder obtained after centrifugation, and precipitate at 50 °C. O After drying in a vacuum drying oven at C for 10 h, the mixture was properly ground to obtain a BTA@UiO-66(Zr) composite material (with a BTA loading of 1%).
[0032] 1.3 Preparation of RL, RL / UiO-66(Zr) and RL / BTA@UiO-66(Zr) coatings
[0033] 1wt%, 2wt%, 3wt% and 5wt% (ratio of raw lacquer weight) of UiO-66(Zr) and BTA@UiO-66(Zr) materials were added into raw lacquer (RL) and stirred quickly until uniform. A 75μm film applicator was used to coat the films on glass sheets and tinplate sheets of different specifications, and then the films were placed in an environment with relative humidity of 60%, 75%, 85% and 98%, respectively. After curing, the modified raw lacquer coating was obtained. The raw lacquer films with RL / UiO-66(Zr)-n and RL / BTA@UiO-66(Zr)-n were named RL-Un and RL-BU-n, respectively, where n represents the percentage of UiO-66(Zr) and BTA@UiO-66(Zr) added relative to RL.
[0034] 2 Results Analysis
[0035] 2.1 Analysis of UiO-66(Zr) and BTA@UiO-66(Zr) catalytic materials
[0036] 2.1.1XRD analysis
[0037] Figure 1The XRD diffraction patterns of UiO-66(Zr) and BTA@UiO-66(Zr). According to the literature search, the main characteristic diffraction peak of UiO-66(Zr) is located at 2θ=7.4 O and 8.6 O The XRD curves of UiO-66(Zr) in the figure all show their characteristic diffraction peaks, indicating that the UiO-66(Zr) material has been successfully prepared. In addition, by observing the image, it can be seen that the diffraction peak positions of BTA@UiO-66(Zr) and UiO-66(Zr) are basically the same, but the intensity of individual diffraction peaks is slightly reduced, which may be due to the fact that BTA is highly dispersed in the framework gap of UiO-66(Zr) and the loading amount is not much.
[0038] 2.1.2 FT-IR analysis
[0039] Figure 2 The infrared spectra of UiO-66(Zr) and BTA@UiO-66(Zr) are shown in the following figure. -1 The peak that appears is the vibration absorption peak of Zr-O. By observing the infrared spectra of UiO-66(Zr) and BTA@UiO-66(Zr), it is found that -1 、511cm -1 The Zr-O vibration absorption peak appears at 3420cm -1 There is a hydroxyl vibration peak at 1548cm -1 、1397cm -1 The peak at -COO stretching vibration absorption peak is shown in Figure 2. We further observed that the infrared spectra of UiO-66(Zr) and BTA@UiO-66(Zr) were basically the same, without peak shift and impurity peaks, but the peak intensity of BTA@UiO-66(Zr) was slightly weaker than that of UiO-66(Zr), which may be due to the fact that BTA was encapsulated in the voids of UiO-66(Zr) and the structure of UiO-66(Zr) remained unchanged. Therefore, it can be preliminarily proved that BTA was encapsulated in UiO-66(Zr) material to make BTA@UiO-66(Zr).
[0040] 2.1.3SEM analysis
[0041] Figure 3This is the SEM image of UiO-66 (Zr). It can be seen from the figure that the UiO-66 (Zr) material is similar to a regular dodecahedron, with a diameter of about 1-2um, and has a fairly stable multi-dimensional framework structure. The porous and dense structure can better play its carrier role and provide stable and abundant active centers. The high-density particle distribution can effectively curb the movement of particles, making the material have a high surface activity and more stable output catalytic effect.
[0042] 2.2 Analysis of RL, RL-U and RL-BU coatings
[0043] 2.2.1 Curing analysis
[0044] In the process of lacquer film formation catalyzed by lacquer, moisture is an important factor in the solidification of the lacquer liquid, so changes in humidity will also affect the reaction rate. Since lacquer is a biological protease, its catalytic activity is greatly affected by external environmental conditions and needs to be kept under specific conditions (20–30 O C and 80% RH–90% RH) can catalyze the raw lacquer to form a film. Therefore, in actual use, raw lacquer is often subject to the temperature and humidity of the environment. For example, in winter, the temperature is low and the humidity is high, while in summer, the temperature is high and the humidity is low. In order to expand the scope of use of raw lacquer so that it is not limited by the ambient temperature and humidity, the raw lacquer needs to be rapidly polymerized to form a film in a wider relative humidity range.
[0045] The humidity in the south is relatively high in winter, generally around 60%, so the present invention first investigates the effect of the amount of catalyst on the drying time of RL, RL-U and RL-BU paint films under a relative humidity of 60%. As shown in Table 1, RL has not achieved surface drying and actual drying for as long as 1176 hours, while the surface drying time and actual drying time of the paint film with the addition of 1wt% UiO-66 (Zr) catalyst are significantly shortened to 28h and 72.5h, respectively, and it is found that with the increase in the amount of catalyst added, the paint film curing time first shows a trend of significantly decreasing and then slightly increasing. When the amount of catalyst added is 3wt%, the time required for the paint film to cure is the shortest, which is 16h and 22h, respectively. BTA@UiO-66 (Zr) catalyst can also catalyze the rapid polymerization of raw lacquer, and the effect of the amount of catalyst added on the paint film curing time is similar to that of UiO-66 (Zr) catalyst, and also shows a trend of first decreasing and then increasing. When 3wt% catalyst was added, the film curing time was the shortest, and the surface drying time of RL-BU-3 was 17h, which was about 0.023 of the surface drying time of RL, and the actual drying time was reduced from >1176h to 20h. The above results show that metal organic framework materials can be used to catalyze the polymerization of raw paint.
[0046] Table 1 Effect of catalyst addition on paint film curing time at relative humidity of 60%
[0047]
[0048] According to the above results, when the addition amount of UiO-66(Zr) and BTA@UiO-66(Zr) is 3wt%, the catalyst has the most significant effect on catalyzing the polymerization of raw lacquer. Therefore, in the following tests, the addition amount of the catalyst is fixed at 3wt%.
[0049] In addition, based on the above, we further investigated the effect of humidity on the curing performance of the paint film, and the results are shown in Table 2. When the relative humidity is 60%, the raw lacquer liquid has not dried on the surface after 1176 hours. As the humidity increases, the time required for the paint film to dry gradually shortens. When the relative humidity is 98%, the surface drying and actual drying times required for the raw lacquer liquid to dry naturally are 5 hours and 6.5 hours, respectively. Under the conditions of relative humidity of 60%, 75% and 85%, the curing time of the raw lacquer liquid with the addition of UiO-66(Zr) and BTA@UiO-66(Zr) catalysts is significantly shortened compared with RL. When the relative humidity is 60%, the actual drying time of RL-U-3 and RL-BU-3 is 22h and 20h respectively. When the relative humidity is 75%, RL-U-3 and RL-BU-3 can be completely cured into film within 16h. When the relative humidity is increased to 85%, the actual drying time is 8h. When the relative humidity is further increased to 98%, the time required for curing is 5.5h, which is still slightly lower than the self-polymerization time of raw lacquer.
[0050] The above results show that the MOF-based catalyst constructed by the present invention can catalyze the rapid polymerization of raw lacquer under different humidity conditions, which is expected to solve the problem of raw lacquer being limited by humidity. In addition, under the same humidity conditions, the polymerization time of raw lacquer catalyzed by UiO-66(Zr) and BTA@UiO-66(Zr) is not much different, indicating that the introduction of the corrosion inhibitor does not change the catalytic performance of the catalyst.
[0051] Table 2 Curing data of RL, RL-3 and RL-BU-3 at different humidity
[0052]
[0053] 2.2.2 FE-SEM analysis
[0054] Figure 4The SEM images of RL, RL-3, and RL-BU-3 coatings at 75% RH, 85% RH, and 98% RH are shown in Figure 1. The number of pores in the coatings a1, b1, and c1 cured at 75% RH does not change significantly, and the number of pores in a2, b2, and c2 decreases at 85% RH, indicating that the catalyst works at 85% RH, and the catalytic effect of BTA@UiO-66(Zr) is more obvious than that of UiO-66(Zr). When the relative humidity is increased to 98% RH, the number of pores in the coatings a3, b3, and c3 does not change significantly due to the addition of different catalysts; however, in the figure, the same coating at different relative humidities is compared vertically, and it is found that the number of pores in the coating at 85% RH is always less than that at 75% RH and 98% RH.
[0055] The holes in the SEM image of the coating are caused by the evaporation of water in the coating. The more water the coating stores, the more oxygen will be dissolved. Under oxygen-rich conditions, the catalytic polymerization time of the coating is extended and accelerated, thereby accelerating the speed of the paint film solidification. The formation of holes will lead to the exposure of the substrate, causing the substrate to contact the environmental medium and cause corrosion. Therefore, the fewer the number of holes, the stronger the water storage capacity of the coating, and the stronger the curing and anti-corrosion ability of the coating. From the above analysis, it can be preliminarily judged that the curing and anti-corrosion effect of the anti-corrosion coating is better at 85% RH.
[0056] 2.2.3 FT-IR analysis
[0057] Based on the above analysis, it is preliminarily judged that the curing and anti-corrosion effects of the anti-corrosion coating will be more significant under 85% RH, so the paint film performance under this humidity condition is tested. Figure 5 The infrared spectra of RL, RL-U-3 and RL-BU-3 coatings cured at 85% RH are shown in the figure. -1 and 1274cm -1 The stretching absorption peak of urushiol-OH exists at all locations, but the peak intensity of the RL-U-3 coating is reduced, indicating that the number of hydroxyl groups on the benzene ring of urushiol is reduced. The infrared curve of RL-U-3 has the peaks at 2853, 1455, and 721 cm -1 The alkyl absorption peak intensity at 991 cm -1 The conjugated diene absorption peak at 1594 cm -1 The carbon-carbon double bond on the benzene ring at the IR curve of RL is also reduced to varying degrees, indicating that the conjugated double bonds of the lacquer side chain have undergone addition homopolymerization. The characteristic peak of the isolated double bond of raw lacquer (-CH=CH-) is 2925cm -1The infrared curves of RL-U-3 and RL-BU-3 coatings also weakened to varying degrees, indicating that the composite anti-corrosion coating underwent oxidative cross-linking, causing the linear molecules in the raw lacquer to bond and cross-link to form a three-dimensional network structure. The infrared absorption peaks of RL-U-3 and RL-BU-3 coatings did not show any new absorption peaks compared to RL, indicating that no new substances were produced during the curing of the composite anti-corrosion coating. 2.2.4 Physical and mechanical properties test analysis
[0058] Table 3 is a table of physical and mechanical properties of RL, RL-U-3 and RL-BU-3 coatings after curing at 85% RH. It can be seen from the table that the roughness of RL-U-3 is somewhat lower than that of RL, while the roughness of RL-BU-3 is reduced to 1.510μm compared with 2.263μm of RL-U-3, indicating that the coating with the addition of BTA@UiO-66(Zr) catalyst is smoother; the impact resistance of RL-U-3 is slightly higher than that of RL, while the impact resistance of RL-BU-3 is 5cm higher than that of RL-U-3; the hardness of RL and RL-U-3 is 4H, while the hardness of RL-BU-3 is increased to 5H; the elasticity of RL-U-3 and RL-BU-3 is increased by 0.5mm compared with RL. Although the glossiness of RL-U-3 and RL-BU-3 is not significantly different from that of RL, the roughness, adhesion, elasticity, impact resistance and hardness of RL-U-3 are all improved compared with those of RL, while the roughness, elasticity and impact resistance of RL-BU-3 are better than those of RL-U-3.
[0059] Therefore, the addition of catalyst did not destroy the excellent physical and mechanical properties of RL coating, while the introduction of corrosion inhibitor improved some of the physical and mechanical properties, making the physical and mechanical properties of RL-BU-3 coating the best.
[0060] Table 3 Physical and mechanical properties test table of RL, RL-U-3, RL-BU-3 coatings
[0061]
[0062]
[0063] 2.2.5 Chemical corrosion resistance test analysis
[0064] Table 4 shows the chemical corrosion resistance test data of RL, RL-U-3 and RL-BU-3 coatings immersed in different solutions. As can be seen from Table 4, the acid resistance of RL-U-3 and RL-BU-3 is higher than that of RL. RL has wrinkled, cracked or corroded on the third day after being immersed in 10wt% H2SO4, while RL-U-3 and RL-BU-3 have not wrinkled, cracked or corroded on the seventh day; RL, RL-U-3 and RL-BU-3 have wrinkled, cracked or corroded on the third day after being immersed in 10wt% NaOH and 95wt% C2H5OH, indicating that the coatings do not have strong alkali resistance and organic solvent resistance; but RL, RL-U-3 and RL-BU-3 have no change after being immersed in 5wt% NaCl on the seventh day, which shows that all coatings have strong salt resistance.
[0065] Therefore, the addition of catalyst did not reduce the salt and organic solvent resistance of the RL coating, and the acid resistance of the composite anti-corrosion coating was improved.
[0066] Table 4 Chemical corrosion resistance test table of RL, RL-U-3, RL-BU-3 coating
[0067]
[0068] “+” indicates that the paint film is not wrinkled, cracked or corroded, and “-” indicates wrinkled, cracked or corroded. 2.2.6 EIS analysis
[0069] Figure 6 The impedance diagrams of RL, RL-U-3 and RL-BU-3 coatings after curing at 85% RH and soaking in 3.5% NaCl solution for different time periods are shown in Figure 1. As can be seen from Figure 2, when the coating is soaked for 24 hours, the impedance curves of RL, RL-U-3 and RL-BU-3 show an increasing trend, and the anti-corrosion effect of RL-BU-3 even reaches 3.5*10 6 The shape of the impedance arc can determine the shielding effect of the coating on electrolyte ions. Therefore, in the same corrosion environment, the larger the impedance arc, the better the corrosion resistance. From b, it can be seen that the impedance arcs of RL-U-3 and RL-BU-3 at 96h are still larger than that of RL, and the impedance arc of RL-BU-3 is about twice as large as that of RL-U-3. From c, it can be seen that the impedance arc of RL at 168h is no longer in an arc shape, indicating that the coating has no anti-corrosion effect, but the impedance arc of RL-BU-3 is still larger than that of RL-U-3. From d, it can be seen that at 216h, RL-U-3 has no anti-corrosion ability, while RL-BU-3 still has 1.5*10 5The arc resistance is of the same magnitude. Therefore, the anti-corrosion duration and anti-corrosion performance are: RL-BU-3 coating>RL-U-3 coating>RL coating. This shows that the addition of catalyst has significantly improved the anti-corrosion performance and duration of the raw lacquer, and the introduction of BTA has further improved the corrosion inhibition rate of the substrate.
[0070] 2.2.7 Tafel curve analysis
[0071] Figure 7 Figure 5 is the Tafel curve of RL, RL-U-3 and RL-BU-3 after being cured at 85% RH and immersed in 3.5% NaCl solution for 0.5 h; Table 5 is the corresponding Tafel parameters of RL, RL-U-3 and RL-BU-3.
[0072] observe Figure 7 It can be seen that both the corrosion current and voltage are: Fe>RL>RL-U-3>RL-BU-3. In general, the Tafel curve is used to judge the ability of the coating sample to protect the substrate by the size of the corrosion current and voltage. Under the same corrosion environment, the smaller the corrosion current and voltage values, the smaller the corrosion tendency of the coating in the corrosion environment, indicating that the anti-corrosion effect of the coating on the metal is: RL-BU-3>RL-U-3>RL. From the analysis of Table 5, it can be seen that the Rp value of RL-U-3 is 8.9725*10 higher than that of RL. 7 Ω / cm 2 Increased to 1.6247*10 9 Ω / cm 2 , and the Rp value of RL-BU-3 is 5.7 times that of RL-U-3; the larger the Rp value in the Tafel parameter, the better the anti-corrosion effect.
[0073] Combined with the chart analysis, the coating has a certain anti-corrosion effect on the metal substrate. The addition of catalyst makes the anti-corrosion performance of raw lacquer better. The introduction of BTA also further improves the anti-corrosion performance of the composite anti-corrosion coating on metal. The analysis results are consistent with the EIS analysis results.
[0074] Table 5 Tafel parameters of RL, RL-U-3 and RL-BU-3 coatings
[0075]
[0076]
[0077] 3 Summary
[0078] (1) Characterization by XRD, FT-IR, FE-SEM, TG and other methods combined with literature data showed that UiO-66(Zr) and BTA@UiO-66(Zr) materials were successfully prepared.
[0079] (2) By examining the curing time of the paint film at different humidity and addition amount of the catalyst and the electron microscopic analysis of the paint film, it can be seen that the addition of the catalyst enables the raw lacquer liquid to catalyze rapid polymerization in a wider relative humidity range (R=60%-98%), and when the catalyst addition amount is 3wt%, the paint film curing time is the shortest; analysis of the physical and mechanical properties test shows that the addition of UiO-66 (Zr) catalyst improves the roughness, adhesion, elasticity, impact resistance and hardness of the raw lacquer; through the chemical corrosion resistance test characterization, it can be seen that the addition of the catalyst does not destroy the salt resistance and organic solvent resistance of RL, but improves the acid resistance of RL; the impedance diagram and Tafel curve of the electrochemical test show that the anti-corrosion performance of RL-BU-3 is improved compared with RL-U-3, and the anti-corrosion time is also extended; This shows that the introduction of BTA optimizes the anti-corrosion effect of the composite anti-corrosion coating and significantly improves the corrosion inhibition rate of the metal substrate.
[0080] In summary, the present invention utilizes the unique physical and chemical properties of metal organic framework materials (MOF) to develop a catalyst for catalyzing the polymerization of raw lacquer. The MOF material UiO-66 (Zr) was successfully prepared by a solvothermal method. On this basis, the porous properties of the MOF material were further utilized to introduce the corrosion inhibitor BTA as a carrier to obtain the BTA@UiO-66 (Zr) material. These two catalysts replaced lacquer enzymes to catalyze the film formation of raw lacquer.
[0081] Compared with natural raw lacquer, the raw lacquer liquid with the addition of UiO-66(Zr) and BTA@UiO-66(Zr) catalysts can quickly polymerize into film under a wider relative humidity range (R=60%-98%); the RL / BTA@UiO-66(Zr) composite anti-corrosion coating that can release BTA can improve the anti-corrosion performance and anti-corrosion duration of RL and RL / UiO-66(Zr) coatings; the physical and mechanical properties (hardness, roughness, impact resistance, elasticity) of the RL / BTA@UiO-66(Zr) composite anti-corrosion coating are also significantly better than those of RL and RL / UiO-66(Zr) coatings.
[0082] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. Application of a zirconium-based metal organic framework material in the preparation of a raw lacquer polymerization catalyst, characterized in that: The zirconium-based metal organic framework material is UiO-66 (Zr).
2. The use according to claim 1, characterized in that: The preparation method of UiO-66(Zr) is as follows: zirconium chloride and terephthalic acid are dissolved in anhydrous DMF solution, and then the solution is placed at 120 O C for 24 h, and after natural cooling, the solid was washed and centrifuged several times with methanol, dried, and finally placed at 120 O C in a vacuum drying oven for 12 h to obtain UiO-66(Zr).
3. The use according to claim 1, characterized in that: The zirconium-based metal organic framework material is used as a carrier, and a corrosion inhibitor is added and encapsulated in the material.
4. The use according to claim 3, characterized in that: The corrosion inhibitor includes benzotriazole BTA.
5. The use according to claim 4, characterized in that: The packaging process is as follows: UiO-66(Zr) was dissolved in DMF solution, and then BTA was added and mixed evenly. The mixture was stirred at room temperature for 12 h, and then centrifuged and washed with methanol several times. The solid powder obtained after centrifugation was collected and heated to 50 °C. O C in a vacuum drying oven for 10 h and ground to finally obtain the BTA@UiO-66(Zr) composite material.
6. Use of the raw lacquer polymerization catalyst as claimed in any one of claims 1 to 5 in the preparation of quick-drying raw lacquer.
Citation Information
Patent Citations
Functionalized metal-organic framework material and preparation method and application thereof
CN111978554A
High-performance curing agent and preparation method thereof and application of high-performance curing agent in epoxy anticorrosive coating material
CN113480912A